2018
DOI: 10.1007/s00128-018-2272-1
|View full text |Cite
|
Sign up to set email alerts
|

Persistent Organochlorine Contaminant Residues in Tissues of Hedgehogs from Turkey

Abstract: The residues of persistent organochlorinated pollutants (POPs), namely polychlorinated biphenyls (PCBs) and organochlorine pesticides (OCPs) (HCHs, CHLs, HCCPs, DDTs, and dicofol congeners) were investigated in the hair and muscle of road-killed Erinaceus roumanicus and E. concolor in Turkey. Mean residue levels were as follows: in hair, PCBs = 7.43 ± 4.88 ng/g and OCPs = 9.21 ± 1.27 ng/g; in muscle, PCBs = 30.73 ± 2.51 ng/g and OCPs = 145.04 ± 16.59 ng/g. There was no significant difference between species an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 41 publications
1
7
0
Order By: Relevance
“…Bird feathers were analyzed with the same methodology as performed on cat hair in the present study. In addition, the distribution pattern of contaminats found in the present study was similar to the one observed in other mammal's hair samples (leopard cat, musk deer, wolf, amur hedgehog, and raccoon dog) from Russia (DDT > PCB > HCB) (Iatrou et al, 2019), but different from hedgehogs from Turkey (PCB > DDT > HCH) (Arıkan et al, 2018), polar bear from East Greenland (PCB> HCH) (Jaspers et al, 2010), and European hedgehog from Belgium (HCB > HCH > DDT > PCB) (D'Havé et al, 2006).…”
Section: Status and Potential Sources Of Contaminationsupporting
confidence: 86%
See 1 more Smart Citation
“…Bird feathers were analyzed with the same methodology as performed on cat hair in the present study. In addition, the distribution pattern of contaminats found in the present study was similar to the one observed in other mammal's hair samples (leopard cat, musk deer, wolf, amur hedgehog, and raccoon dog) from Russia (DDT > PCB > HCB) (Iatrou et al, 2019), but different from hedgehogs from Turkey (PCB > DDT > HCH) (Arıkan et al, 2018), polar bear from East Greenland (PCB> HCH) (Jaspers et al, 2010), and European hedgehog from Belgium (HCB > HCH > DDT > PCB) (D'Havé et al, 2006).…”
Section: Status and Potential Sources Of Contaminationsupporting
confidence: 86%
“…Due to their adverse effects on the environment and wildlife, the monitoring of POPs has thus become increasingly important for exposure and risk assessment (Hung et al, 2016) (Alleva et al, 2006). Previous studies have shown that POPs can be effectively measured in mammalian hair (Arıkan et al, 2018;González-Gómez et al, 2018;Iatrou et al, 2019;Jaspers et al, 2010). This non-destructive biomonitoring approach induces minimal stress to the sampled individuals, allows investigation of contamination levels in possibly endanger species or threatened populations, is ethically acceptable, cost-effective, and easily applicable to both human and animal samples (Ali et al, 2013;Jaspers et al, 2019;Poma et al, 2020;Schramm, 2008;Sonne et al, 2020;Sun et al, 2019) Iran has a remarkable diversity of wild cats.…”
Section: Introductionmentioning
confidence: 99%
“…In other words, the species order by means of OCP accumulation is in strong agreement with their ecological relations (Coat et al, 2011) and trophic levels (Alleva et al, 2006). The studies related to OCP residues in the keratinous tissue of mammals (Arıkan et al, 2018a) and birds (Arıkan et al, 2017;Arıkan et al, 2018b) in Turkey show that DDTs are at the highest levels when compared with other congeners. Studies on OCP residues in bird feathers from different countries support our findings that DDTs and congeners have the highest residue among other OCP congeners similar to the case of Turkey (Dauwe et al, 2005;Behrooz et al, 2009;Eulaers et al, 2013).…”
Section: Discussionmentioning
confidence: 55%
“…Adipose tissue (Kutz et al, 1991), muscle (Arıkan et al, 2018a), blood, and internal organs such as kidney and liver (Kenntner et al, 2003;Dhananjayan, 2013) were the tissues sampled most for pollutant determination in wild animals. However, using these vital tissues of animals for the determination of pollutants faces practical and ethical issues because of the possible negative impact of such testing on the species (Furness, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the high lipophilicity of PCBs leads to bioaccumulation in individuals and the food chain (Wong et al, 2012), and PCBs cause a series of adverse effects on multiple organs, including powerful carcinogenic properties, cognitive and behavioral abnormalities, disorganized autoimmunity, and increased risk of metabolic diseases both in animals and in human (Crinnion, 2011; Knerr & Schrenk, 2006). PCBs could accumulate in the muscle of animals and human (Arıkan et al, 2018; Chu et al, 2003). Studies in 1990s showed that decreased total lean mass and lower body weight in human were associated with prenatal PCBs exposure (Guo et al, 1994; Jacobson et al, 1990), suggesting that skeletal muscle (SM) may be the target of PCBs.…”
Section: Introductionmentioning
confidence: 99%